First Principles Study of Bonding Mechanisms at the TiAl/TiO2 Interface - Alexander V. Bakulin; Sergey S. Kulkov; Svetlana E. Kulkova; Stephen Hocker; Siegfried Schmauder (Metals, 2020)
The adhesion properties of the TiAl/TiO2 interface are estimated in dependence on interfacial layer composition and contact configuration using the projector augmented wave method. It is shown that a higher value of the work of separation is obtained at the interface between the Ti-terminated TiAl(110) surface and the TiO2(110)O one than at that with the Al-terminated alloy. An analysis of structural and electronic factors dominating the chemical bonding at the interfaces is carried out. It is shown that low bond densities are responsible for low adhesion at both considered interfaces, which may affect the spallation of oxide scale from the TiAl matrix.